Portfolio Strategy of Pangeran Group Using BCG Matrix - Winona, Vanya; Wandebori, Harimukti (Journal of Business and Management, 2012)
This research is made to develop one of Hospitality company group based on family business. The companies that will be discussed are companies that are domiciled in Sumatra such as PT Ustano, PT Istano Pangeran Permai, and PT Hotel Pangeran Pekanbaru. The owner of these three companies is still too involved in the operational activities of the company. The expansion and development of the companies was delayed for several years because the owners were focusedin taking care of the existing companies. In addition, these three companies are still run individually and still not centralized. Finally, the works become ineffective and the owners already realized about that. The owner of these three companies already felt that these companies need a holding or parent company so that the company will run effectively.Actually researcher was doing this research using formulation and implementation of strategic management theories. But, this paper only focuses on BCG Growth-Share Matrix and GE Business Screen to analyze the portfolio strategy of ‘Pangeran’ Group.Purpose:The purpose of this research is to identify the positions of ‘Pangeran’ Group’s subsidiaries to determine the strategies that will be implemented after. Design/methodology/approach:The theories that needed for this research are Portfolio Strategy. These theories mostly collected from Strategic Management and Business Policy Book by Wheelen and Hunger (2006). Researcher used multiple sources of evidence, which combining a lot of data to get valid results for the methodology. To collect the data, interviews, observation, and group discussion forum conducted to the owner as well as several corporate management teams. In addition, researcher also collected secondary data for comparison purpose.Findings:According to BCG Growth Share Matrix, all of Pangeran Group business occupies the Stars position in which Business Growth rate and Relative Competitive Position is high. But if viewed from Business Growth rate point of view, actually Pangeran Pekanbaru Hotel is placed in the critical position and situation, which nearly moved to Cash Cows quadrant.From the GE Business Screen, those three companies are still in the Winner position and placed in the top left corner that symbolizes the Industry Attractiveness and Business strength are still strong. From the portfolio analysis results of this analysis can be concluded that Pangeran Group are in a very good position.Research limitations/implications (if applicable):Things that will be examined are the issues that related with the effectiveness of those three companies. The Observation would be done with interviewing the owners of ‘Pangeran’ Hotels. The respondents that will be interviewed are already expert with the current situation of ‘Pangeran’ Hotels.Practical implications:The implication of this research is to know the profile of the business and to make the resource allocation.Originality/value:This paper consists of portfolio analysis, which is one of method to access a corporate strategy. This research will be useful for the development of the corporate.Keywords-component; Portfolio Strategy; BCG Growth-Share MatrixCategory: Corporate Strategy